Three weeks of eccentric training combined with overspeed exercises enhances power and running speed performance gains in trained athletes - Cook, C. J.; Beaven, C. M.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2013)
Eccentric and overspeed training modalities are effective in improving components of muscular power. Eccentric training induces specific training adaptations relating to muscular force, whereas overspeed stimuli target the velocity component of power expression. We aimed to compare the effects of traditional or eccentric training with volume-matched training that incorporated overspeed exercises. Twenty team-sport athletes performed 4 counterbalanced 3-week training blocks consecutively as part of a preseason training period: (1) traditional resistance training; (2) eccentric-only resistance training; (3) traditional resistance training with overspeed exercises; and (4) eccentric resistance training with overspeed exercises. The overspeed exercises performed were assisted countermovement jumps and downhill running. Improvements in bench press (15.0 ± 5.1 kg; effect size [ES]: 1.52), squat (19.5 ± 9.1 kg; ES: 1.12), and peak power in the countermovement jump (447 ± 248 W; ES: 0.94) were observed following the 12-week training period. Greater strength increases were observed as a result of the eccentric training modalities (ES: 0.72-1.09) with no effect of the overspeed stimuli on these measures (p > 0.05). Eccentric training with overspeed stimuli was more effective than traditional resistance training in increasing peak power in the countermovement jump (94 ± 55 W; ES: 0.95). Eccentric training induced no beneficial training response in maximal running speed (p > 0.05); however, the addition of overspeed exercises salvaged this relatively negative effect when compared with eccentric training alone (0.03 ± 0.01 seconds; ES: 1.33). These training results achieved in 3-week training blocks suggest that it is important to target-specific aspects of both force and movement velocity to enhance functional measures of power expression.